2018
DOI: 10.1177/1010428318773652
|View full text |Cite
|
Sign up to set email alerts
|

Sperm associated antigen 9 (SPAG9) a promising therapeutic target of ovarian carcinoma

Abstract: SPAG9 is a novel tumor associated antigen, expressed in variety of malignancies. However, its role in ovarian cancer remains unexplored. SPAG9 expression was validated in ovarian cancer cells by real time PCR and Western blot. SPAG9 involvement in cell cycle, DNA damage, apoptosis, paclitaxel sensitivity and epithelial- mesenchymal transition (EMT) was investigated employing RNA interference approach. Combinatorial effect of SPAG9 ablation and paclitaxel treatment was evaluated in in vitro. Quantitative PCR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Our recent study also revealed similar observation that showed increased cytotoxicity with paclitaxel in SPAG9 knockdown ovarian cancer cells. 30 Yet another study also showed that knockdown of CDK11 increased ovarian cancer cell death when treated along with paclitaxel. 37 However, increased paclitaxel cytotoxicity in AKAP4 downregulated TNBC cells requires in-depth understanding of molecular pathways and warrants further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study also revealed similar observation that showed increased cytotoxicity with paclitaxel in SPAG9 knockdown ovarian cancer cells. 30 Yet another study also showed that knockdown of CDK11 increased ovarian cancer cell death when treated along with paclitaxel. 37 However, increased paclitaxel cytotoxicity in AKAP4 downregulated TNBC cells requires in-depth understanding of molecular pathways and warrants further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Combinatorial effect of AKAP4 shRNA and paclitaxel in different combinations was examined in MDA-MB-231 cells as described earlier. 30 Combination index (CI) values were assessed using CompuSyn 1.01 software (ComboSyn, Inc., Paramus, NJ, USA). The experiments were carried out in triplicates three independent times.…”
Section: Measurement Of Synergistic Effectmentioning
confidence: 99%
“…In line with this, reduced proliferation mediated by p21, which drives G1 growth arrest, led to resistance to taxanes in eight ovarian cancer cell lines that showed an EMT-signature. Indeed, it is well known that proliferating cells respond better than quiescent cells to taxanes [122].…”
Section: Emt and Chemotherapy Resistancementioning
confidence: 99%
“…SPAG9 belongs to the cancer testis antigen (CTA) family, which represents a unique class of tumor antigens with normal expression in the testis and aberrant expression in various malignancies [34]. It has been identified as a promising biomarker for early detection and a therapeutic target for several cancers, including ovarian, cervix, breast and renal cell carcinoma [35][36][37][38][39]. MGST is a membrane protein localized to the endoplasmic reticulum and outer mitochondrial membrane, where it serves a protective function.…”
Section: Discussionmentioning
confidence: 99%